Spatial-temporal change of the geomagnetic field: environmental aspect - M.I. Orlyuk; A.A. Romenets (Геофизический журнал, 2020)
The geomagnetic field, along with other environmental factors, is a necessary component of life on the Earth. Currently, there are relevant ecological standards for the values of constant and variable fields. Taking them into account, it is possible to determine the conditions necessary for the normal functioning of biological objects in general and humans in particular. In a number of regulations, certain limit values for a constant magnetic field are introduced, as well as the maximum permissible time of a human being stay in such fields. In this regard, the article considers the spatiotemporal change in induction B on the Earth’s surface using the example of its main magnetic field according to the international model IGRF-13 for the time interval 1950—2020. In more detail for this time interval, the induction module B and its perturbation were analyzed for geomagnetically different regions that are, namely, the territories of Ukraine, of Yamal (Russia) and around the Ukrainian Antarctic Akademik Vernadsky station. For the planet in whole, a significant decrease in the geomagnetic field is shown, against the background of which its sharp jumps are observed (in 1960—1965, 1980—1985 and in 2000—2005), and after 2005 to the present, a deceleration in the decrease of the geomagnetic field is observed. Against the background of a decrease in the geomagnetic field of the planet, areas with extreme changes both in the direction of increase (Ukraine, Yamal) and decrease (AV station) are distinguished. The spatiotemporal changes in the geomagnetic field detected on the Earth’s surface determine the structure and dynamics of its magnetosphere, which by-turn affects the nature of the interaction with it of solar wind substance and of cosmic radiation, as well as the flow altitudes of magnetospheric and ionospheric currents. According to the distribution of the geomagnetic field anomalies on the surface of the planet, as well as to their changes over the studied time interval, regions with different (as compared with proposed ecological norms) values of the constant magnetic field and its disturbances are distinguished. In particular, for the epoch of 2020, for the territory in the vicinity of the AV station, the induction vector module B is on average 15,000 nT less than its value for the territory of Ukraine and 25,000 nT — of Yamal. Significant changes in the geomagnetic field were determined: an increase of 1765 nT for Ukraine, 1418 nT for Yamal and a decrease of — 7081 nT in the vicinity of AV station. At the same time, the perturbation of the geomagnetic field of the territory of Ukraine is within its ecological norm, deviates from it in the direction of increase on the Yamal Peninsula, and near the AV station it will soon go beyond its limits in the direction of decrease, while maintaining modern field changes.